Pemanfaatan Sampah Organik Sebagai Media Budidaya Lalat BSF untuk Mengurangi Pencemaran Lingkungan - Kusuma, Yudha Adi; Sudarni, Dyan Hatining Ayu; Nalurita, Bunga Trisnis (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The implementation of organic waste management through the utilisation of black soldier fly (BSF) cultivation media has been employed in Ngraket Village, Balong District, Ponorogo Regency, with the objective of reducing environmental pollution. The community service activity spanned four weeks and included socialization, practice, and evaluation. Black soldier fly (BSF) larvae utilize organic waste as feed, producing economically valuable residue for livestock nutrition. N-Gain test results demonstrated a significant increase in partner knowledge, exceeding 76%, confirming the effectiveness of the program. BSF utilization is expected to support waste reduction, prevent pollution, and increase village income. Follow-up activities are proposed to support the sustainability of this program.